Physeal distraction prior to excision of metaphyseal malignant bone tumors in children: Preserving joint function and limb growth - María García-Carrasco; Carla Carbonell-Rosell; Denisse G. Loya de la Cerda; Marius Aguirre-Cañadell; Roberto Veléz-Villa (Clinical Surgical Oncology)
Background: Improvements in imaging methods and adjuvant chemotherapy have increased survival rates in children with bone sarcomas up to 80%, therefore long-lasting limb salvage procedures are needed. Purpose: To describe a case series of pediatric patients who have undergone physeal distraction prior to tumor resection for treatment of metaphyseal malignant bone tumors. Methods: Between January 2007 to December 2020, 8 patients (5 boys and 3 girls) with a mean age of 7.2 years (2–13), underwent physeal distraction as the first stage of a tumor resection protocol. Six patients had Ewing's sarcoma and two had osteosarcoma. Tumor locations were: proximal tibia (4 cases), distal femur, proximal humerus, distal radius, and distal fibula (1 case each). The affected bones were replaced with cadaver allograft in 6 patients; there was also one fibula autograft and one vascularized fibula graft. Chemotherapy was administered pre- and post-surgery; one patient received adjuvant radiotherapy. Average follow-up was 62.6 months (8–152). Results: Physeal distraction lasted an average of 10.6 days (3–15); delay to definitive resection was 17 days (range 13–22). Mean length of resection was 10.7 ​cm (range 5–14) and all had negative margins. There were no local recurrences. Three patients suffered disease progression with metastasis and died. Surgical complications included: pin infection (1 patient), surgical site infection (2 patients), allograft fracture (1 patient), and nonunion of the diaphyseal junction (3 patients). Final lower limb length discrepancy was 1.5 ​cm (range 1–2 ​cm). Normal joint function was achieved in 6 patients. The mean MSTS score was 75% (53%–97%). Conclusions: Physeal distraction technique is an oncologically safe limb salvage procedure with good functional results, and it should be considered in the treatment of metaphyseal pediatric malignant tumors.